2020
DOI: 10.3390/ma13112494
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Light Irradiation on the Photocatalytic Degradation of Organic Pollutants

Abstract: The design of a photocatalytic process must consider intrinsic and extrinsic parameters affecting its overall efficiency. This study aims to outline the importance of balancing several factors, such as radiation source, total irradiance, photon flux, catalyst substrate, and pollutant type in order to optimize the photocatalytic efficiency. Titanium oxide was deposed by the doctor blade technique on three substrates (microscopic glass (G), flour-doped tin oxide (FTO), and aluminum (Al)), and the photocatalytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 45 publications
3
10
0
Order By: Relevance
“…The similar photocatalytic efficiency for all the series up to 4 h of light irradiation may be ascribed to the accumulation of adsorbed pollutants and the produced dye decomposition products onto the specimens' surface, which could partially inactivate the reaction sites [44]. Nonetheless, by increasing the light exposure period up to 8 h, the The similarity of the results reveals that the difference in coating time does not extensively influence the photocatalytic efficiency.…”
Section: Influence Of the Tio2 Coating Rates On The Photocataytic Efficiencymentioning
confidence: 75%
See 1 more Smart Citation
“…The similar photocatalytic efficiency for all the series up to 4 h of light irradiation may be ascribed to the accumulation of adsorbed pollutants and the produced dye decomposition products onto the specimens' surface, which could partially inactivate the reaction sites [44]. Nonetheless, by increasing the light exposure period up to 8 h, the The similarity of the results reveals that the difference in coating time does not extensively influence the photocatalytic efficiency.…”
Section: Influence Of the Tio2 Coating Rates On The Photocataytic Efficiencymentioning
confidence: 75%
“…The similar photocatalytic efficiency for all the series up to 4 h of light irradiation may be ascribed to the accumulation of adsorbed pollutants and the produced dye decomposition products onto the specimens' surface, which could partially inactivate the reaction sites [44]. Nonetheless, by increasing the light exposure period up to 8 h, the reaction products generated by the degradation mechanism had enough time to be removed from the surface of the specimen, and the TiO 2 nanoparticles could be reactivated in order to degrade a higher quantity of pollutants.…”
mentioning
confidence: 85%
“…From the data presented, it can be observed that the time required to remove MET from solution decreases with increasing irradiance. The increase in MET photodegradation efficiency can be explained by the conversion of total irradiance to photon flux, which was involved in the photocatalytic radical generation processes OH • and O •− 2 [65]. The application of irradiance of 250 W m −2 , corresponding to the daily GHI for Poland, does not allow the complete removal of MET from the solution within 60 min.…”
Section: Effect Of Irradiance Intensity On the Efficiency Of Photocatalysis Processmentioning
confidence: 99%
“…Three of the total eight articles [ 1 , 2 , 3 ] are focused on TiO 2 -based photocatalysts, as TiO 2 has been extensively studied as a low-cost and environmentally friendly material with relatively high photocatalytic activity and excellent chemical stability.…”
mentioning
confidence: 99%
“…In Reference [ 1 ], TiO 2 (Degussa P25) films were deposited using the doctor blade technique on three different substrates: microscopic glass (G), flour-doped tin oxide (FTO) and aluminum (Al). The photocatalytic properties of the samples were tested on two pollutants, tartrazine (Tr) dye and acetamiprid (Apd) insecticide, under UV-A, UV-B + C and VIS irradiations (seven scenarios) for 8 h. In order to optimize the photocatalysis efficiency, the influence of several parameters (irradiation source, total irradiance value, photon flux, catalyst substrate and pollutant type) were studied.…”
mentioning
confidence: 99%